Advances in Food Analysis - Gentili, Alessandra (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This Topical Collection of Molecules provides the most recent advancements and trends within the framework of food analysis, confirming the growing public, academic, and industrial interest in this field. The articles broach topics related to sample preparation, separation science, spectroscopic techniques, sensors and biosensors, as well as investigations dealing with the characterization of macronutrients, micronutrients, and other biomolecules. It offers the latest updates regarding alternative food sources (e.g., algae), functional foods, effects of processing, chiral or achiral bioactive compounds, contaminants, and every topic related to food science that is appealing to readers. Nowadays, the increasing awareness of the close relation among diet, health, and social development is stimulating demands for high levels of quality and safety in agro-food production, as well as new studies to fill gaps in the actual body of knowledge about food composition. For these reasons, modern research in food science and human nutrition is moving from classical methodologies to advanced instrumental platforms for comprehensive characterization. Nondestructive spectroscopic and imaging technologies are also proposed for food process monitoring and quality control in real time.